Latin American Spanish phrasebook & dictionary (Lonely Planet phrasebooks, 2015)
Lonely Planet Latin American Spanish Phrasebook & Dictionary is your handy passport to culturally enriching travels with the most relevant and useful Latin American Spanish phrases and vocabulary for all your travel needs. With language tools in your back pocket, you can truly get to the heart of wherever you go, so begin your journey now!